Cohort changes in educational disparities in smoking: France, Germany and the United States. (February 2015) - Pampel, Fred; Legleye, Stephane; Goffette, Céline; Piontek, Daniela; Kraus, Ludwig; Khlat, Myriam
Abstract: This study investigates the evolution of educational disparities in smoking uptake across cohorts for men and women in three countries. Nationally representative surveys of adults in France, Germany and the United States in 2009–2010 include retrospective measures of age of uptake that are compared for three cohorts (born 1946–1960, 1961–1975, and 1976–1992). Discrete logistic regressions and a relative measure of education are used to model smoking histories until age 34. The following patterns are found: a strengthening of educational disparities in the timing of uptake from older to younger cohorts; an earlier occurrence of the strengthening for men than women and for the United States than France or Germany; a faster pace of the epidemic in France than in the United States, and; a divide between the highest level of education and the others in the United States, as opposed to a gradient across categories in France. Those differences in smoking disparities across cohorts, genders and countries help identify the national and temporal circumstances that shape the size and direction of the relationship between education and health and the need for policies that target educational disparities. Highlights: Earlier emergence of educational disparities in smoking in the United States than in France and Germany. Faster pace of the tobacco epidemic in France than in the United States. Divide between the highest level of college education and the others in the United States. Gradient across the educational categories in France. Remaining gender differences greatest in the United States.